Selection of long-term herbs and their grass mixtures for fodder farmlands - Nasiyev, B. N.; Tlepov, A. S.; Salauatova, N. G. (Zhangir khan West Kazakhstan agrarian-technical university, 2017)
For the uninterrupted provision of agricultural animals with complete feed, the cultivation of perennial grasses in single-species and mixed crops is important. The researches revealed productivity of perennial grasses in various crops. Featured agrophytocenoses of perennial grasses can provide the production of high protein feed in forage farmlands of West Kazakhstan region.
Наука и образование. - № 3 (48). 2017.
Keywords: кормление животных; корма для животных; многолетние травы; смешанные посевы; агрофитоценозы; научный журнал; отечественное издание; периодическое издание